Pengaruh Pemahaman Aswaja An-Nahdliyyah terhadap Sikap Toleransi di KB Pertiwi Pondoksalam Kabupaten Purwakarta - Ulfa Nurul Ieda; Mohamad Ramdhan; Ligar Meilasari; Dewi Dahlianti; Muhamad Wirahadikusumah; Imam Asrofi (Journal Innovation In Education, 2025)
This study aims to describe and analyze the influence of understanding Ahlussunnah wal Jama’ah (Aswaja) An-Nahdliyyah values on interreligious tolerance attitudes among early childhood students at KB Pertiwi Pondoksalam, Purwakarta. Early childhood education is considered a strategic phase or “golden age” for instilling fundamental character values that support children’s mental and spiritual development. This research used a qualitative approach with a descriptive case study design. The research subjects consisted of teachers and children aged 4–6 years, while the research focus was on the implementation of Aswaja values and the manifestation of tolerance attitudes in students’ daily behavior. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The results show that Aswaja An-Nahdliyyah values are implemented through daily habituation, teacher role modeling, Islamic moral storytelling, and group play activities. Understanding key Aswaja values, particularly tasamuh (tolerance), tawassuth (moderation), and i’tidal (fairness), has a positive influence on the development of children’s tolerance attitudes. This is reflected in behaviors such as mutual respect, the absence of discriminatory actions toward peers, cooperation in group activities, and the habitual use of polite language in daily interactions. Overall, education based on Aswaja An-Nahdliyyah values plays an important role in laying the foundation for religious moderation and inclusive attitudes from an early age.